Devaluation and balance of payments in ECOWAS countries : a study in the review of Nigeria's exchange rate policy - Ozumba, C. C. (Lagos : Central Bank of Nigeria)
This paper provides an evaluation and balanace of payments in ECOWAS countries with a particular study in the review of Nigeria's exchange rate policy between 1973 to 1978.
Includes bibliographical references
lje 04/03/2019
Arch
Keywords: Exchange rate; Balanace of payments; Economic Community of West African States (ECOWAS); Nigeria